2017
DOI: 10.5539/ies.v10n6p159
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Assessment on the Evaluation Process of Students

Abstract: This study aims at finding out the effect of peer assessment on the evaluation process of students. The hypothesis underlying this study is that assessment is an integral part of the learning process, which should play an important role in the educational model. The current study will emphasize the importance of using peer assessment as a tool to engage students in the evaluation process, clarify the role of peer assessment in promoting student learning, diversify the scope of the evaluation through the framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 18 publications
2
25
0
2
Order By: Relevance
“…According to this, the scores given by the peers conform with those scores given by the instructor regarding both methods. This result parallels the research findings of other studies in the literature (Alzaid, 2017;Napoles, 2008;Şahin, 2008). Falchikov and Goldfinch (2000) carried out a meta-analysis using 48 quantitative peer assessment studies comparing peer and teacher marks; they found that the mean correlation between the marks given by peers and the instructor was .69 across all the studies within the meta-analysis.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 91%
“…According to this, the scores given by the peers conform with those scores given by the instructor regarding both methods. This result parallels the research findings of other studies in the literature (Alzaid, 2017;Napoles, 2008;Şahin, 2008). Falchikov and Goldfinch (2000) carried out a meta-analysis using 48 quantitative peer assessment studies comparing peer and teacher marks; they found that the mean correlation between the marks given by peers and the instructor was .69 across all the studies within the meta-analysis.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 91%
“…More importantly, PA is seen by many researchers as a way of giving more control and autonomy to students. It involves them actively in the feedback process as opposed to a passive reliance on teacher's feedback to 'fix' up their writing (Alzaid, 2017). The findings of this study confirmed that PA can improve EFL learners' writing skills by allowing them to assume responsibility for other students' and their own learning which is in line with previous research (Topping, 2017).…”
Section: Conclusion and Recommendationssupporting
confidence: 89%
“…Hal tersebut dapat meningkatkan konsep pembelajaran antar mahasiswa, pembelajaran kolaboratif, dan pembelajaran pemecahan masalah. Alzaid (2017) menambahkan dalam penelitiannya dengan memberikan rekomendasi untuk perkembangan pendidikan yang modern, dosen didorong untuk memulai menilai mahasiswa dengan pembelajaran partisipatif yaitu dengan peer assessment atau peer review. Penelitian ini bertujuan untuk menguji apakah student peer-review assessment dapat berjalan efektif khususnya dilakukan di mata kuliah praktikum.…”
Section: Pendahuluanunclassified